Step-by-Step Fabrication of PVDF-TiO2 Hollow Fiber Membrane and Its Application Desalination of Wetland Saline Water via Pervaporation - M. Mahmud; Muthia Elma; Aulia Rahma; Nurul Huda; Riani Ayu Lestari; Awali S. K. Harivram; Erdina L. A. Rampun; Mohd H. D. Othman; Muhammad Roil Bilad (Universitas Pendidikan Indonesia, 2023)
Wetland water is opted as the source of domestic water supply when the availability of clean fresh water is scarce. Wetland water requires proper treatment due to the high concentration of organic matter and high salinity, particularly in the dry season. This research aims to synthesize, characterize, and investigate the performance of polyvinylidene fluoride (PVDF)-TiO2 hollow fiber membrane for wetland saline water desalination via pervaporation. The PVDF-TiO2 hollow fiber membranes were fabricated through the dry wet spinning method under various air gaps (10, 15, and 20 cm). Then, the resulting membranes were tested in a pervaporation process at temperatures of 25, 40, and 60°C. Results show that the incorporation of TiO2 into the PVDF matrix imparted hydrophilicity properties into the resultant membranes. The presence of TiO2 was confirmed by the TiO2 stretching vibration at 1640 cm-1 (FTIR) and the TiO2 phase at diffraction peaks at 25.5 and 37°. The membranes exhibited the highest water flux (7.48 kg/m2.h) and salt rejection ( 99.5%) at 40°C. Overall, the developed PVDF-TiO2 hollow fiber membranes showed encouraging results and demonstrated their effectiveness for the desalination of wetland saline water.